Influence of oxidative stress on functional-morphological changes in dental pulp - Zarzecka, Joanna; Dyduch-Dudek, Wioletta (Journal of Stomatology, 2017)
Reactive oxygen species play a key role in the basic biological processes taking place in the human body. However, the excessive activity of these molecules together with concomitant oxidative stress impairs the morphological-functional functions of the system, including by having a negative impact on dental pulp. These processes lead to oxidation of the proteins and lipids present in the matrix cells of dental pulp. As a result of changes, many cells may lose or change their biological functions. The cells most prone to such changes are odontoblasts and fibroblasts in the endodontium. Changes in the structure of collagen and non-collagen proteins not only disrupt connective tissue homeostasis, but also impair defensive reactions when dental pulp trauma or inflammation occur. Blood vessels and nerves are also damaged. As a result, this can lead to lesions in the dentin-pulp complex, trigger pulpitis and accelerate tissue aging in the endodontium. However, the body possesses defence mechanisms that protect against exposure to oxygen free radicals. The enzymatic anti-oxidative protection offered by saliva is of great importance here.